ChemInform Abstract: Efficient and Selective Azidation of per‐O‐Acetylated Sugars Using Ultrasound Activation: Application to the One‐Pot Synthesis of 1, 2, 3‐Triazole Glycosides. Issue 45 (November 2015) - Marzag, Hamid; Alaoui, Soukaina; Amdouni, Hella; Martin, Anthony R.; Bougrin, Khalid; Benhida, Rachid
Abstract An inexpensive, simple, and highly efficient process is developed for the selective anomeric azidation of protected sugars using ultrasound activation and an of iron catalyst.